Flow-through comb electroporation device for delivery of macromolecules - Adamo, Andrea (2013)
We present a microfluidic electroporation device with a comb electrode layout fabricated in polydimethylsiloxane (PMDS) and glass. Characterization experiments with HeLa cells and fluorescent dextran show efficient delivery (~95%) with low toxicity (cell viability ~85%) as well as rapid pore closure after electroporation. The activity of delivered molecules is also verified by silencing RNA (siRNA) studies that demonstrate gene knockdown in GFP expressing cells. This simple, scalable approach to microfluidic, flow-through electroporation could facilitate the integration of electroporation modules within cell analysis devices that perform multiple operations.